The Position of Pancasila in the Development of Legal Theory (From Legal Formality to Legal Realism): A Case Approach - Yuli Prasetyo Adhi; Priyono, FX. Joko (Indonesian Journal of Pancasila and Global Constitutionalism, 2025)
This article aims to analyze the position of Pancasila in the legal context in Indonesia and analyze the judge's decision with the Pancasila corridor. The judge's decision has considerations and a legal basis in it. The legal basis used by judges is the applicable laws and regulations. Meanwhile, we have Pancasila as the source of all legal sources, which means that the position of Pancasila is above the laws and regulations. Pancasila has values that are used as a guideline for community life. Then, how is the position of Pancasila in the development of legal theory and how Pancasila becomes a legal ideal and is used as a basis for deciding a case in court. One of the decisions used in this paper is a decision related to the exoneration clause. The analysis of Decision No. 400/Pdt/2019/PT SBY was conducted using the view of legal formality and the view of legal realism. The analysis was conducted using doctrinal research methods. This article has a novelty, namely criticizing positivism in Indonesia and offering Pancasila as a living law and integrating Pancasila in the case approach in the judge's decision. This article has theoretical implications as an enrichment of legal theory in Indonesia, making Pancasila the basis for the development of Indonesian state legal theory, and strengthening the legal paradigm. The practical implication is that there is an analysis of Pancasila's views in the judge's decision No. 400/Pdt/2019/PT SBY.